Підвищення рівня капіталізації банків України на основі корпоративного управління - Банах, Ю. В.; Слобода, Л. Я. (Видавництво Львівської політехніки, 2010)
Досліджено проблему управління банківським капіталом, підвищення рівня його якості та достатності, щоб забезпечити економічне зростання країни в умовах подолання кризових явищ, оцінено рівень капіталізації банків України на основі аналізу статистичних показників функціонування банківської системи, обґрунтовано вплив корпоративного управління на процеси формування капіталу банків, запропоновано заходи щодо підвищення капіталізації банків України на основі удосконалення корпоративного управління. Main problems of management banking capital, improvement of level of its quality and sufficient is outlined for providing of the economy growing, banking activities corporate management improvement are defined in the article. The level of capitalization of Ukrainian banks on the basis of analysis of statistical indexes of function the banking system is conducted. Influence of corporate management on the processes of forming of capital of banks is grounded. The measures on the increase of level capitalization Ukrainian banks on the basis of improvement of corporate management, elements of corporate management strategy and main criteria of its efficiency evaluation are determined.
Keywords: банки; банківський капітал; капіталізація банків; рівень капіталізації; якість капіталу; структура капіталу; банківський нагляд; корпоративне управління; банківські ризики; banking institutions; bank capital; capitalization of banks; level of capitalization; quality of capital; capital structure; banking supervision; corporate management; banking risks